Ruta graveolens and its active constituent rutin protect against diethylnitrosamine-induced nephrotoxicity through modulation of oxidative stress - Ayman M. Mahmoud, Rasha R. Ahmed, Hanan A. Soliman, Marwa Salah (Journal of Applied Pharmaceutical Science, 2015)
The current study was designed to evaluate the possible protective effects of Ruta graveolens (Rue) and its active phenolic constituent rutin against diethylnitrosamine (DEN)-induced nephrotoxicity in rats. A single dose of DEN (200 mg/kg body weight) was intraperitoneally injected. Two-weeks after DEN administration, rats received 0.05 % phenobarbital in drinking water for 12 weeks. Ruta graveolens (50 mg/kg) and rutin (50 mg/kg) were orally administered from the first day of experiment. DEN administration induced kidney injury evidenced by histological alterations as well as significant increase in serum urea (P
Keywords: Rue, Flavonoids, Renal injury, Oxidative stress, Antioxidants.